Penyuluhan Pengelolaan Sampah terhadap Peningkatan Pengetahuan dan Tindakan Anggota Dasawisma Dusun VI Pleret, Panjatan, Kulon Progo - Venta Apryllanda; Yamtana Yamtana; Siti Hani Istiqomah (Sanitasi: Jurnal Kesehatan Lingkungan, 2021)
Domestic waste management nowadays is frequently not appropriate with methods and techni- ques which are environmentally friendly, included in Dusun VI of Pleret Village in Panjatan, Kulonprogo. Therefore, effective counseling methods are needed for up-levelling the related knowledge and practice among the community. This study was aimed to identify the effect of counseling method with demonstration technique and poster media on the knowledge and prac- tice of dasawisma members in Dusun VI on their domestic waste management. The study was a quasi experiment with non-equivalent control group design. Sixty four women dasawisma mem- bers are randomly allocated into treatment group or control group based on their domiciles. Both groups consisted of equal number of respondents. To measure the knowledge and practice, a test instrument and a check-list which were tested for their validity and realibility beforehand, were employed. Because the study data did not fulfill normal distribution assumption, a non- parametric, Wilcoxon test was employed to analyze at 0,05 significance level. The study results show that because of the counseling method with demonstration and poster, the knowledge and practice scores are significantly different between pre-test aand post-test (the corresponding p values are 0,037 and 0,006, subsequently).